QUEM EXPLICA O QUÊ, PARA QUEM E COMO? A EXPLICAÇÃO DA CRISE ENERGÉTICA BRASILEIRA EM 2001 SEGUNDO OS TELEJORNAIS - Araújo, Denise Lino De (Intercâmbio, 2010)
This paper aims at discussing the way to news programs explain the power crisis (blackout). The theoretical fields of Applied Linguistics, Journalism and Educations are concerned. The analysis shows that both programs play a didatic role on informing the shortage goals to the public.